An exploration of the impact of AIDS-related losses and role changes on grandmothers - Burt, Mary (Rhodes University, Faculty of Humanities, Department of Psychology, 2004)
The US Bureau of the Census (1999) projected that by 2004, 14 million people in sub-Saharan Africa will develop full blown AIDS, making this region by far the largest disease burden in the world (World Health Organization, 2002). The United Nations AIDS Programme judged South Africa to have the leading number of people living with HIV/AIDS worldwide (World Health Organisation, 2002). To date there has been extensive research conducted on the socio-economic impacts of HIV/AIDS on families in Africa. However an area of investigation that has remained largely underreported is the inquiry into the psychological impacts of HIV/AIDS on elderly caregivers. In African families older women increasingly have to provide care to their adult children with AIDS and their orphaned grandchildren. However few research studies have assessed the experience of parental caregiving and its psychological impacts on these women. This qualitative research study hypothesised that the role of primary parental caregiver in fact causes a range of psychologically distressing states, which serve to compromise the psychological well-being of these caregivers. To investigate this hypothesis three Xhosa speaking women living in informal settlements in Grahamstown, in the Eastern Cape Province of South Africa were selected for the study. The women were interviewed by means of semi-structured interviews, which consisted of questions related to their caregiving experiences, their experiences of loss, their choice of coping strategies, the role of support networks and their experiences of foster care responsibilities. The interviews were transcribed and analysed using a grounded hermeneutic approach. The research results confirmed the working hypothesis. The research revealed that although it was considered culturally appropriate for older women to care for their children and grandchildren, their caregiver roles caused significant psychological distress. Their distress was related to: emotional and physical exhaustion, complicated grief reactions and ongoing emotional and physical upheaval related to foster care responsibilities. Based on the results, the research recommendations emphasised the need for continual awareness of the psychological implications of caregiving for older African women with the aim to preserve their capacity to function as the primary caring resource to families struck by HIV/AIDS.
Keywords: HIV infections -- Social aspects -- South Africa -- Eastern Cape; HIV infections -- Economic aspects -- South Africa -- Eastern Cape; AIDS (Disease) -- Social aspects -- South Africa -- Eastern Cape; AIDS (Disease) -- Economic aspects -- South Africa -- Eastern Cape; AIDS (Disease) -- Patients -- Care -- South Africa -- Eastern Cape; Bereavement -- Psychological aspects -- Eastern Cape; Foster parents -- South Africa -- Eastern Cape; Loss (Psychology); Grandmothers -- South Africa -- Psychology